(Afterword) Riska: memories of a Dayak girlhood - Colfer, C.J.P. (1999)
This brief afterward discusses Riska’s experiences in the context of Colfer’s ethnographic knowledge of gender and lifestyle changes among the dayaks of Kalimantan. It discusses the burgeoning literature reflecting women’s voices, a genre to which Riska contributes. Building on her own ethnographic experience, Colfer highlights important changes that have affected women’s lives, such as increasing wage labour opportunities for men, new technological devices for men, negative stereotypes of dayaks on the part of outsiders, and agricultural extension programs that focus on men. The problems that dayaks often encounter when they try to join mainstream Indonesian life are briefly discussed. She concludes by recounting some of the important positive values represented by dayak ways of life: a sense of humor and equanimity in the face of disaster; unusual generosity; recognition of differing strengths; acceptance of responsibility of reach other’s welfare;and a value placed on hard work, initiative and creativity.